Evaluation of potential fuel savings by introducing formation flight on a North Atlantic scenario - Marks, Tobias; Linke, Florian; Gollnick, Volker (2015)
The work presented in this paper deals with the evaluation of potential fuel savings gained by the introduction of formation flight on a North Atlantic scenario. In order to perform this evaluation, it is assumed that the formation flight takes place on dedicated Formation Corridors that correspond with the North Atlantic Tracks of the Organized Track System and that the first aircraft types equipped with the necessary formation flight systems will be the ones that are most frequently used. With these assumptions the most common aircraft type used on the North Atlantic in westbound direction along with the 20 most frequented connections served by this type of aircraft are identified for a specific week based on historical data. In a next step, a surrogate model to calculate the formation flight benefits is derived for a two-aircraft formation consisting of this aircraft type. Based on this model for all possible combinations of the connections the optimal Formation Corridors in terms of chosen track and flight level are identified using graph-based optimization techniques together with inefficiency metrics to evaluate the benefits of the formations. In a subsequent detailed trajectory analysis for all the identified optimal formations the actual fuel savings are calculated. Statistical analysis shows that considerable fuel savings can be obtained for all connection combinations. Furthermore it is shown, that the declaration of one dedicated Formation Corridor will result in substantial fuel savings for a considerable amount of the evaluated connection combinations.